Case Report: Complete response after tislelizumab treatment in a hepatocellular carcinoma patient with abdominal lymph node metastasis - Deng, Haihui; Chen, Bin; Peng, Deti; He, Jian; Zhao, Weicheng; Chen, Tuantuan; Xie, Zonggui; Pang, Fuwen (Frontiers in Immunology, 2023)
Background Abdominal lymph node (ALN) metastasis is associated with a poor prognosis in patients with hepatocellular carcinoma (HCC) because of the limited number of effective therapeutic options available. Immunotherapy with immune checkpoint inhibitors, such as those targeting programmed death receptor-1 (PD-1), have produced encouraging results in patients with advanced HCC. Here, we report a complete response (CR) in a patient with advanced HCC and ALN metastasis after combination treatment with tislelizumab (a PD-1 inhibitor) and locoregional therapy. Case summary A 58-year-old man with HCC experienced progressive disease with multiple ALN metastases after undergoing transcatheter arterial chemoembolization (TACE), radiofrequency ablation (RFA), and laparoscopic resection. Because the patient did not wish to receive systemic therapy, including chemotherapy and targeting therapy, we prescribed tislelizumab (as a single immunotherapeutic agent) together with RFA. After four tislelizumab treatment cycles, the patient achieved a CR without tumor recurrence for up to 15 months. Conclusion Tislelizumab monotherapy can be effectively used to treat advanced HCC with ALN metastasis. Moreover, the combination of locoregional therapy and tislelizumab is likely to further increase therapeutic efficacy.